Super games of the generals - Alvarez, Antonio Jr. P. (1995)
The Super Games of the Generals, basically is a computer adaptation of the board game Games of the Generals with many additional features such as making it multi-player and having alliances. It aims to provide entertainment to (network) users. This network applications software is also intended to give it's developers the much background of the rapidly progressing field of computer networking. The SGG software is a product of the groups' ten months of designing, researching, programming, testing, and re-engineering. Initially, the group laid the new set of rules for SGG, regardless of implementation issues (problems). The next step was to design the needed data structures and procedures. Alongside, the group had to acquire knowledge in networking through intensive research, both in the theoretical and programming aspect. Next was the programming and the (dreaded) testing phase. Finally, the integration of the different modules into the end product. Needless to say, several problems were encountered by the group specially with the implementation phase (i.e. programming and testing), most of which were beyond the control of the group. Modifications with regards to the design had to be made as the need arises. However, inspite of the seemingly insurmountable obstacles, the group was able to satisfy most of the software's original design specifications through a lot of patience and plenty of hardwork.